What young people want from their diabetes team: developing a patient reported experience measure (PREM) for young people with type 1 diabetes. (May 2015) - Girling, Isabella; Day, Emma; Fazakerley, Kate; Gray, Tat; Hindmarsh, Peter; Musgrove, Neil; Rahman, Shakeel; Trevelyan, Nicola; Warner, Justin; Christie, Deborah; On behalf of the Royal College of Paediatrics Child Health the National Paediatric Diabetes Audit Patient Reported Experience Measure working group
Abstract The objectives of this study were: to explore whether a patient reported experience measure (PREM) questionnaire for carers reflected aspects of the clinic experience important to young people; and to develop a PREM for young people with type 1 diabetes (T1D) to measure their clinic experience. A cross‐sectional study design and focus groups were used. Questions from a PREM for carers and four open‐ended questions were incorporated into a semi‐structured interview administered to 77 young people with T1D across four paediatric diabetes clinics. Eighty‐two percent of young people rated help in managing high and low blood glucose as the most important aspect of their clinic experience. All items identified by parents as important were rated important by over two‐thirds of young people, with the exception of 'How important is it to be seen on your own?' (40% rated this as important). Thematic analysis identified two superordinate themes: learning new information, and age appropriate structure and communication. Exemplary quotations from each theme were converted into questions and reviewed by six young people using cognitive interviewing. The final question set was reviewed by the National Paediatric Diabetes Audit PREM working group. The PREM was distributed to 177 paediatric diabetes units in England and Wales for completion between September 2012 and January 2013. Exploring what is important for a young person about their clinic experience has supported the construction of a paediatric‐centred measure. The young person PREM creates opportunities for improvement in care to help diabetes teams listen to patients and work with them to provide the best possible service. Copyright © 2015 John Wiley & Sons.